2016
DOI: 10.3390/w8080312
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Performance and the Predictive Capacity of Build-Up and Wash-Off Models on Different Temporal Scales

Abstract: Stormwater quality modeling has arisen as a promising tool to develop mitigation strategies. The aim of this paper is to assess the build-up and wash-off processes and investigate the capacity of several water quality models to accurately simulate and predict the temporal variability of suspended solids concentrations in runoff, based on a long-term data set. A Markov Chain Monte-Carlo (MCMC) technique is applied to calibrate the models and analyze the parameter's uncertainty. The short-term predictive capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
(58 reference statements)
0
5
0
1
Order By: Relevance
“…The ranges of the EMC for the roads were defined based on the minimal and maximal EMC values calculated over twelve samples collected at the boulevard Alsace Lorraine's inlet during the experimental campaign. Previous analysis of these values showed that they are higher than EMCs calculated for other road catchments due to the site's high traffic density [11]. However, some of the road segments in the catchment are not necessarily frequented at the same density as the boulevard; therefore, their loadings of TSS might be lower.…”
Section: Tss Loadsmentioning
confidence: 84%
See 3 more Smart Citations
“…The ranges of the EMC for the roads were defined based on the minimal and maximal EMC values calculated over twelve samples collected at the boulevard Alsace Lorraine's inlet during the experimental campaign. Previous analysis of these values showed that they are higher than EMCs calculated for other road catchments due to the site's high traffic density [11]. However, some of the road segments in the catchment are not necessarily frequented at the same density as the boulevard; therefore, their loadings of TSS might be lower.…”
Section: Tss Loadsmentioning
confidence: 84%
“…Even when parameters are optimized, a high level of uncertainty is associated with their calibrated values [13], revealing important challenges in defining sampling ranges for water quality parameters. The sampling ranges of the EMC for roads were defined by measurements collected at the inlet of the main boulevard within the catchment [11], while intervals for roof surfaces were determined by available data provided in the literature [3]. The boundaries of the sampling ranges for SWMM wash-off parameters C 1 and C 2 correspond to the lowest and highest values obtained from the best cases investigated in an earlier study conducted within the same catchment [11].…”
Section: Boundaries Of the Sampling Rangesmentioning
confidence: 99%
See 2 more Smart Citations
“…The results were summarized according to the median coefficient values because the Alternative Fit experienced two instances where k 1 was substantially higher than for the rest of the tests. Others have also observed convergence to optimum values that diverge substantially from the mean or have no clear physical significance (Al Ali et al., 2016). Additionally, the coefficient structure is computationally easier to fit using statistical software packages than the nested exponentials in the SWMM Fit and likely contributes to its higher AIC value.…”
Section: Discussionmentioning
confidence: 99%